P11.18.A Localizing value of EEG recordings in patients with glioblastoma. (5th September 2022) - Silvaieh, S; Marko, M; Trimmel, K; Zulehner, G; Berghoff, A; Preusser, M; Schmook, M; Ulbrich, L; Hainfellner, J A; Widhalm, G; Rössler, K; Berger, T; et al.
Abstract: Background: Glioblastoma is associated with a high risk of epileptic seizures ranging from 40% to 60%. Before the advent of modern imaging techniques, electroencephalography (EEG) was a critical component in evaluating patients with space-occupying lesions. In this retrospective single-center study, we aimed (1) to characterize a cohort of patients with glioblastoma with regards to EEG monitoring, seizure frequency and the frequency of prescribed anti-seizure medications (ASM) and (2) to assess the value of EEG as a localizing technique in patients with glioblastoma. Material and Methods: We reviewed the charts of 179 patients with glioblastomas between January 1st, 2020 and January 1st, 2022, treated at the Medical University of Vienna. The diagnosis was based on MRI and/or confirmed by biopsy according to the 2016 World Health Organization Classification of Tumors of the Central Nervous System. Patients who received an in-house EEG as part of their diagnostic work-up were included if an MRI/CT scan was available (within an average time of +/-60 days). For localization, focal slowing (theta/delta activity) and/or epileptiform discharges were considered. EEG rating was performed by a board-certified electrophysiologist blinded for the diagnosis and MRI/biopsy findings. Results: We included 52 patients (29.05% of screened cohort) with at least one EEG and MRI or CT scan performed before or after EEG, following inclusion criteria (median: 2 days; mean: 6 days; range: -29 to 52), in the final analysis. Clinical seizure activity and/or epileptiform discharges on EEG were detected in 46 patients (88.46%), and 48 patients (92.31%) were on ASM. An IDH-wildtype glioblastoma was diagnosed in 45 patients (86.54%), 4 had an IDH-mutant glioblastoma (7.69%), and in 3 patients, IDH-status was unknown (5.77%). In 22 patients (42.31%), biopsy revealed a positive MGMT promoter methylation status, while 28 were unmethylated (53.84%), and two patients had an unknown MGMT promoter methylation status (3.85%). Intermittent and/or continuous focal slow-wave activity was registered in 45 patients (86.54%). In comparison, epileptiform discharges could only be found in 13 patients (25%). When compared to MRI/CT scans, the hemispheric tumor localization could be determined in 42 cases (80.77%). Moreover, the affected brain lobe was accurately predicted in 35 patients (67.31%). Three patients had diffuse EEG changes (5.77%), and EEG was unremarkable in 7 patients (13.46%). Conclusion: Overall, our presented data indicate that the hemispheric localization of glioblastoma can be reliably predicted by EEG recordings, while a precise (brain lobe-specific) localization was only possible in around two-thirds of cases.